GIAT BISNIS BUSANA DALAM PERSPEKTIF HUKUM ISLAM - Abu Alim; Agus Sudradjat (Constitutum: Jurnal Ilmiah Hukum, 2024)
In today's modern world, business is a more promising endeavor to achieve profits and income. Islam as a religion has always accompanied sharia values throughout the ages, including in business. The fashion business which is included in basic needs has become a big thing and has become one of the focuses of entrepreneurs to create and produce clothing with various models and types. Clothing can build a culture that is quite influential in human life throughout the ages, and culture is also what ultimately leads to a level of human dignity or not, therefore it is also hoped that entrepreneurs will not only pay attention to the profits (profits) obtained but also really It is necessary to be expected to pay attention to the benefits of the business it operates with the models, styles and types of clothing it will produce. Islam pays great attention to neat clothing from the perspective of its rules and regulations in order to uphold and maintain human dignity. Therefore, it is a big homework for Muslims, especially for those who are business people in the fashion sector, to really pay attention not only to aesthetic values, but also to ethical values that make humans more civilized and beneficial. This journal uses qualitative research using library research methods (Library Research) and uses secondary data in the form of books, journals and other relevant scientific works. With this research, it is hoped that entrepreneurs in the fieldof fashion products can become a reference for designs and models that will be produced and consumed by the public.